Governing energy: Asia’s future and the G20 - FLORINI, Ann (Institutional Knowledge at Singapore Management University, 2014)
Asia’s future peace and prosperity depend on whether it can solve its energy challenges. The region’s striking economic growth in recent decades has been – literally – fueled by massive and reckless development of fossil fuel-based energy systems, in ways that are clearly unsustainable. The costs, in environmental devastation, damage to health, and geopolitical instability, are high and growing, and increasingly unnecessary as new technologies reach a transformative tipping point. But new technologies alone will not change the current grim realities. Such change requires overcoming enormous vested interests, deeply entrenched practices, and above all habits of thought and assumptions. And here, oddly enough, Asia may find help at the G20 – if the G20 can be imaginative enough.